Densidade, seleção de micro-habitat e distribuição de Phylloscartes eximius (Aves: Tyrannidae) - Tonetti, Vinicius Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Basic information about the biology of the taxa is scarce, even for endangered ones, which hinders the development of conservation strategies. Data on population density and size are among the most important for the conservation of birds. The Southern Bristle-Tyrant (Phylloscartes eximius) is a passerine bird endemic to the Atlantic Forest and its main threat is habitat loss and fragmentation. Its populations are apparently declining, what put it in the Near Threatened global threat category. However, up to date, no systematic study involving its demography has been conducted. Thus, the aim of this chapter was to estimate its density and population size at the Cantareira State Park (CSP), a stronghold for the species at São Paulo State. A hundred fixed sampling points were established within 100 m buffers created around all the CSP trails. During sampling, the distance between the observer and the birds were measured or estimated and, with the help of software DISTANCE 6.2, statistical models were created and fitted to the sampled distances. Between May and December 2014, 46 detections of the species were obtained in 600 points, sampling six times each one of the 100 points, this resulted in estimated values of 12.7 individuals/ km² and abundance of 967 individuals in the CSP. This density value is considered low when compared to other species of the genus (P. kronei; 208 indivíduos/km²), as well as other insectivorous passerines of the Atlantic Forest. As a conservation strategy, studies on the density and demographic structure of the species should be performed at other places of occurrence, and these information must be associated with long-term monitoring of the species

Informações básicas a respeito da biologia dos táxons são escassas, mesmo para os ameaçados de extinção, o que dificulta a elaboração de estratégias de conservação. Dados sobre densidade e tamanho populacional estão entre os mais importantes para a conservação das aves. O barbudinho (Phylloscartes eximius) é um passeriforme endêmico da Mata Atlântica e seus principais fatores de ameaça são a perda e fragmentação de habitat. Acredita-se que esteja sob acentuado declínio populacional, fato que o coloca na categoria de Quase Ameaça em nível global. No entanto, até o momento, nenhum estudo sistemático que envolvesse sua demografia foi realizado. Dessa maneira, o objetivo desse capítulo foi estimar sua densidade e tamanho populacional no Parque Estadual da Cantareira (PEC), uma importante área de ocorrência da espécie no Estado de São Paulo. Foram estabelecidos 100 pontos fixos dentro de buffers de 100 m criados ao redor de todas as trilhas do PEC. Durante as amostragens dos pontos, as distâncias entre o observador e as aves foram medidas ou estimadas e, com auxílio do software DISTANCE 6.2, foram criados então modelos estatísticos, ajustando-os às distâncias amostradas. Entre maio e dezembro de 2014 foram obtidas 46 detecções da espécie em 600 pontos, amostrando cada um dos 100 pontos seis vezes cada, o que resultou nos valores estimados de 12,7 indivíduos/km² e abundância de 967 indivíduos no PEC. Esse valor de densidade é considerado baixo quando comparado com outra espécie do gênero (P. kronei; 208 indivíduos/km²), assim como outros passeriformes insetívoros da Mata Atlântica. Como estratégia de conservação, sugere-se que sua densidade, assim como estudos que visem conhecer sua estrutura demográfica, seja estimada em outros locais de ocorrência. Deve-se também realizar monitoramentos em longo prazo da espécie
Density, microhabitat selection and distribution of Phylloscartes eximius (Aves: Tyrannidae)
Keywords: Birds; Ave; Conservação biológica; Nicho (Ecologia); Mata Atlântica; Parque Estadual da Cantareira (São Paulo, SP)